2022
DOI: 10.1002/ldr.4151
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma‐primed rice straw alters structural and functional properties of sodic soil

Abstract: Sodic soil is increasing due to intensive cropping and imbalanced use of agrochemicals. Therefore, the objective of the present study was to reduce the soil sodicity in agricultural fields using sustainable resources. The 'microbe-residue-soil' interaction is hypothesized to foster the structural and functional changes during sodic soil reclamation. To elucidate the hypothesis, rice straw (RS) assimilation in sodic soil was instated in the presence of synergistically interacting Trichoderma koningiopsis NBRI-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have indicated that inoculated PSB can markedly improve soil properties (Mahdi et al, 2020; Tahir et al, 2018). To a great extent, microorganisms in inoculants may influence plant development and nutrient uptake (Spohn et al, 2020; Tandon et al, 2022; Wong et al, 2022). In this study, we found that inoculated XQP35 and SQP80 treatments significantly increased maize biomass and the relative chlorophyll content (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that inoculated PSB can markedly improve soil properties (Mahdi et al, 2020; Tahir et al, 2018). To a great extent, microorganisms in inoculants may influence plant development and nutrient uptake (Spohn et al, 2020; Tandon et al, 2022; Wong et al, 2022). In this study, we found that inoculated XQP35 and SQP80 treatments significantly increased maize biomass and the relative chlorophyll content (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…colonization in plants may be due to inhibition of Na + uptake. T. asperellum altered the concentration of Nitrogen, a nutrient directly intricate in the composition of chlorophyll (Lawson & Flexas, 2020;Boamah et al, 2021;Tandon et al, 2022).…”
Section: Antioxidant Enzymes Activitiesmentioning
confidence: 99%
“…The colonisation of cucumber roots by T. asperellum has been shown to enhance the availability of phosphorus (P) with a significant enhancement in plant biomass (Yedidia et al, 2001). Moreover, T. harzianum and T. longibrachiatum can improve the solubility of P, iron (Fe), copper (Cu), manganese (Mn), and zinc (Zn) and reduce the fixation of Fe and Cu in soil (Conte et al, 2022;Tandon et al, 2022). It has been shown that Trichoderma spp.…”
Section: Figurementioning
confidence: 99%